Cautionary note about non-linear models in fisheries - ., Prajneshu (Indian Journal of Fisheries, 2011)
A large number of research^ papers in journals dealing with non-linear models in fisheries, if nothing else, is a testimony to the fact that such models play a very important role in this area. For example, studies on length-weight relationship (Ai^anasastry 1989, Dcvadoss 1989. Jayasankar 1989, Premalatha 1989). estimation of fecundi^ (Piska and Waghniy 1989, Hoda and Qureshi 1989) and synthetic models (Kurian 1989), all involve models in which the parameters appear in a non-linear manner.